Bacterial Communities Associated With Healthy and Bleached Crustose Coralline Alga Porolithon onkodes - Fangfang Yang; Zhiliang Xiao; Zhiliang Xiao; Zhangliang Wei; Lijuan Long (Frontiers in Microbiology, 2021)
Crustose coralline algae (CCA) play vital roles in producing and stabilizing reef structures and inducing the settlement and metamorphosis of invertebrate larvae in coral reef ecosystems. However, little is known about the bacterial communities associated with healthy and bleached CCA and their interactions with coral larval settlement. We collected samples of healthy, middle semi-bleached, and bleached CCA Porolithon onkodes from Sanya Bay in the South China Sea and investigated their influences on the larval settlement and metamorphosis of the reef-building coral Pocillopora damicornis. The larval settlement/metamorphosis rates all exceeded 70% when exposed to healthy, middle semi-bleached, and bleached algae. Furthermore, the compositions of bacterial community using amplicon pyrosequencing of the V3–V4 region of 16S rRNA were investigated. There were no obvious changes in bacterial community structure among healthy, middle semi-bleached, and bleached algae. Alphaproteobacteria, Bacteroidetes, and Gammaproteobacteria were dominant in all samples, which may contribute to coral larval settlement. However, the relative abundances of several bacterial communities varied among groups. The relative abundances of Mesoflavibacter, Ruegeria, Nautella, and Alteromonas in bleached samples were more than double those in the healthy samples, whereas Fodinicurvata and unclassified Rhodobacteraceae were significantly lower in the bleached samples. Additionally, others at the genus level increased significantly from 8.5% in the healthy samples to 22.93% in the bleached samples, which may be related to algal bleaching. These results revealed that the microbial community structure associated with P. onkodes generally displayed a degree of stability. Furthermore, bleached alga was still able to induce larval settlement and metamorphosis.